Pemikiran Pembebasan dalam Teologi (Suatu Analisis Historis dan Geografis) - M. Husein A. Wahab (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2013)
Issues on liberation in all religions lead to emerge a lot of thinkers both in  orthodox and modern theology. These issues aims at not making a doctrine or  creed an absolute way of life for a believer or an absolute conduct for a citizen. In  historical perspective, absolute doctrine or creed is usually made by a dictator for  his or her permanently political power. Consequently, a believer or a citizen in  one community is hampered in communication and not tolerant to the other  believer or to other community. This rigid condition, at the end, usually leads to  criticism and protest of some critical thinkers either to the religious elites or the  rulers of one country. To mention, there are some theological liberation sects or  movements: rational theology, transformative theology, contextual theology,  humanism, Dalif and Minjung. In politics, the super power or developed countries  produce maps as geographical perspective to divide, to limit, to control and to rule  under developed countries either in economy, social, cultural and religion. Asia,  Africa and Latin America are supposed to be the third worlds (poor countries)  under the control of super powers as rich countries.